2017
DOI: 10.1007/s00441-017-2595-y
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of ramified CD45 cells in chicken embryo and their contribution to bursal secretory dendritic cells

Abstract: Embryonic tissues contain highly ramified stellate-shaped cells expressing CD45 and MHC II antigens but their origin and immunophenotype are unknown. Using staged avian embryos and cell-type-specific antibodies, we establish a detailed spatiotemporal ontogeny of cells that express CD45, the earliest marker of hematopoietic stem cells in the chick. CD45 immunostaining marks three distinct embryonic cell populations: round, ramified and amoeboid cells. The round and ramified CD45+ cells appear first in yolk-sac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 59 publications
0
19
0
1
Order By: Relevance
“…These cells arise from single pluripotent haematopoietic stem cells (HSCs) from the yolk sac, indicating an extra-embryonic origin of haematopoiesis (Melchers, 2010). In chicken embryos, the presence of a large number of CD2+ cells in the peripheral blood as well as CD45+ cells in the yolk sac of 2-day-old embryos prior to liver and thymus development implies yolk sac origin of immune cells (Zhou et al, 2008;Dóra et al, 2017). Furthermore, the detection of pan-leukocyte antigen (CD45) and αIIb integrin subunit (CD41) on the cells of aortic clusters (and para-aortic foci) suggests the embryo proper as the origin of definitive HSCs (Melchers, 2010).…”
Section: Ontogeny Of Innate Immune System Cells and Their Functional mentioning
confidence: 99%
“…These cells arise from single pluripotent haematopoietic stem cells (HSCs) from the yolk sac, indicating an extra-embryonic origin of haematopoiesis (Melchers, 2010). In chicken embryos, the presence of a large number of CD2+ cells in the peripheral blood as well as CD45+ cells in the yolk sac of 2-day-old embryos prior to liver and thymus development implies yolk sac origin of immune cells (Zhou et al, 2008;Dóra et al, 2017). Furthermore, the detection of pan-leukocyte antigen (CD45) and αIIb integrin subunit (CD41) on the cells of aortic clusters (and para-aortic foci) suggests the embryo proper as the origin of definitive HSCs (Melchers, 2010).…”
Section: Ontogeny Of Innate Immune System Cells and Their Functional mentioning
confidence: 99%
“…While characterizing the distribution and ontogeny of CD45 + hematopoietic cells in the chick embryo, we noted the presence of a ramified CD45 + cell type characteristic of macrophages within the gut mesenchyme (Dóra et al. ). Similar to mammals, chicken CD45 is a transmembrane tyrosine phosphatase protein expressed by all cells of hematopoietic lineage, excluding erythrocytes.…”
Section: Resultsmentioning
confidence: 85%
“…Follicle formation and immigration of B cells are preceded by the immigration of CD45 + /CSF1R + precursors of bursal dendritic cells into follicle buds (14,37). CD45 staining at E12 revealed that CXCR4 + cells are also positive for CD45 and hence of hematopoietic origin.…”
Section: Cxcl12 and Cxcr4 Mrna Expression Vary During Bursa Ontogenymentioning
confidence: 99%
“…Then in a second migration step, those earliest bursal B cells have to migrate from the bursal mesenchyme into developing follicle buds. Formation of these follicle buds is triggered by immigrating precursors of bursal secretory dendritic cells (BSDC), which are of hematopoietic origin and cross the basement membrane under the surface epithelium to induce a so-called dendro-epithelial tissue (13,14). In a third migration step, B cells migrate to the follicle border, when the formerly homogeneous follicles separate into cortex and medulla.…”
Section: Introductionmentioning
confidence: 99%